How well is firn densification represented by a physically based multilayer model? Model evaluation for Devon Ice Cap, Nunavut, Canada. Issue 222 (2014) - Gascon, Gabrielle; Sharp, Martin; Burgess, David; Bezeau, Peter; Bush, Andrew B.G.; Morin, Samuel; Lafaysse, Matthieu
Abstract: Evaluation of how accurately snowpack models can capture hydrological processes in firn is critical to determining how well they will simulate future glacier mass-balance changes. Here we compare simulations using the Crocus snowpack model with the evolving firn stratigraphy recorded in 14 cores drilled at four elevations in the accumulation zone of Devon Ice Cap, Canada, during the 2004–12 period of rapid summer warming. Simulations were forced with a combination of surface observations and reanalysis data. Simulations resulted in positive model bias in near-surface density, and negative bias in density at depth compared to observations. Results point to the importance of incorporating heterogeneous percolation in firn in order to improve the representation of meltwater flow, better reproduce observed firn density and temperature profile evolution, and improve simulations of glacier mass balance during periods of climate warming.